Puffling - Wild, Margaret, 1948- (Feiwel and Friends, 2009)
As his affectionate parents nourish and protect him, a plucky young puffin impatiently waits--but not without some reservations--for the day when he is "strong enough and tall enough and brave enough" to leave his nest on the rocky cliff-face and waddle off to the sea.